A new strategy for developing superior electrode materials for advanced batteries: using a positive cycling trend to compensate the negative one to achieve ultralong cycling stability. Issue 6 (5th October 2016) - Liu, Dai-Huo; Lü, Hong-Yan; Wu, Xing-Long; Wang, Jie; Yan, Xin; Zhang, Jing-Ping; Geng, Hongbo; Zhang, Yu; Yan, Qingyu
Abstract : In this communication, in order to develop superior electrode materials for advanced energy storage devices, a new strategy is proposed and then verified by the (Si@MnO)@C/RGO anode material for lithium ion batteries. Abstract : In this communication, in order to develop superior electrode materials for advanced energy storage devices, a new strategy is proposed and then verified by the (Si@MnO)@C/RGO anode material for lithium ion batteries. The core idea of this strategy is the use of a positive cycling trend (gradually increasing Li-storage capacities of the MnO-based constituent during cycling) to compensate the negative one (gradually decreasing capacities of the Si anode) to achieve ultralong cycling stability. As demonstrated in both half and full cells, the as-prepared (Si@MnO)@C/RGO nanocomposite exhibits superior Li-storage properties in terms of ultralong cycling stability (no obvious increase or decrease of capacity when cycled at 3 A g −1 after 1500 cycles) and excellent high-rate capabilities (delivering a capacity of ca. 540 mA h g −1 at a high current density of 8 A g −1 ) as well as a good full-cell performance. In addition, the structure of the electrodes is stable after 200 cycles. Such a strategy provides a new idea to develop superior electrode materials for next-generation energy storage devices with ultralong cycling stabilities.